Fabrika çalışanlarında yalnızlık, depresyon ve tükenmişliğin incelenmesi - KARACA, SEMRA (My University, 2021)
Amaç: Bu çalışma fabrika çalışanlarında yalnızlık, dep resyon ve tükenmişliğin incelenmesi amacıyla yapıldı. Materyal ve Metot: Tanımlayıcı ve ilişki arayıcı tipteki bu araştırma, İstanbul'da bir iş yerinde yapıldı. Araştırma nın evrenini işyeri çalışanları (N=450), örneklemini ise 265 çalışan oluşturdu. Veriler, Kişisel Bilgi Formu, UCLA Yalnızlık Ölçeği 3. Versiyon, Beck Depresyon Envanteri ve Maslach Tükenmişlik Envanteri ile toplandı. Bulgular: Çalışanların yaş ortalaması 33,99±8,15, % 78.9’u erkek, %51,7’si ilköğretim mezunu, %83,0’ü işçi dir. UCLA yalnızlık ölçeği puan ortalaması 39,83±8,98; BECK depresyon envanteri puan ortalaması 8.06±7.66 ve Maslach Tükenmişlik Envanteri alt boyutlarından; duygu sal tükenme 20,05±7,17, duyarsızlaşma 8,78±3,94, kişisel başarı puan ortalaması 27,90±6,26’dır. Çalışanların UCLA yalnızlık ölçeği, BECK depresyon ölçeği ve Maslach Tü kenmişlik Envanteri puanları arasında istatistiksel olarak anlamlı ilişkiler bulunmuştur (p˂0,05). Sonuç: Bu araştırmanın bulguları, çalışanların yalnızlık, depresyon ve tükenmişlik puanlarının ilişkili olduğunu göstermektedir.

Objective: This study was conducted for the purpose of examining loneliness, depression and burnout in the em ployees of factory. Materials and Methods: This descriptive and correlation al research was conducted at a workplace in Istanbul. The universe of the study comprised the employees of the workplace (N=300) and the sample’ consisted of 265 em ployees. The data were collected using the Personal In formation Form, the UCLA Loneliness Scale (Version 3), the and the Beck Depression Inventory and Maslach Burn out Inventory. Results: The mean age of the participants was 33,99±8,15 years. Of the participants, 78,9% were men, 51,7% were elementary school graduates and 83,0% were laborers. The UCLA loneliness scale mean score of the participants was 39,83±8,98; their BECK depression inventory mean score was 8,06±7.66 and out of the subdimensions of the Maslach Burnout Inventory, mean scores for emotional exhaustion were 20,05±7,17, 8,78±3,94 on the desensiti zation and 27,90±6,26 on the personal accomplishment subscales. Statistically significant relationships were found between employees' UCLA loneliness, BECK de pression and Maslach Burnout Inventory scale scores (p˂0,05). Conclusion: The findings of this research show that there are relationships between employees' loneliness, depres sion and burnout scores.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED); Çalışan; depresyon; tükenmişlik; yalnızlık; Burnout; depression; employee; loneliness